2019
DOI: 10.1186/s13601-019-0280-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of TMEM178, which encodes a negative regulator of NFATc1, decreases with the progression of asthma severity

Abstract: In two independent microarray studies involving primary airway epithelial cells, the relative gene expression of TMEM178 decreases with the progression of asthma severity. Our manuscript creates a paradigm for future studies dissecting the role of Tmem178 in the pathogenesis of severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In addition, TMEM178 expression levels decreased significantly with severity of asthma progression. Consistent with our results, Patel et al [6] stated that TMEM178 expression decreases with the increase in asthma severity giving the known role of TMEM178 as a negative regulator of nuclear factor of activated T cells (NFAT). They hypothesized that TMEM178 plays a significant role in NFAT-induced severe asthma inflammation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, TMEM178 expression levels decreased significantly with severity of asthma progression. Consistent with our results, Patel et al [6] stated that TMEM178 expression decreases with the increase in asthma severity giving the known role of TMEM178 as a negative regulator of nuclear factor of activated T cells (NFAT). They hypothesized that TMEM178 plays a significant role in NFAT-induced severe asthma inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…Epithelial genes directly induced in asthma include the transmembrane protein 178 (TMEM178), which is a negative regulator of the nuclear factor of activated T cells (NFAT). Inflammation caused by NFAT is a known actor in asthma pathogenesis [6]. Chloride pathway, calcium activated family member 1 (CLCA1), is associated with mucus hypersecretion, airway hyper reactivity, and hyper eosinophilia in asthma [7], serpin peptidase inhibitor, clade B, member 2 (SERPINB2) (also known as plasminogen activator inhibitor-2) which belongs to the serpin class of proteases and functions through inhibiting plasminogen activation and promoting fibrin formation and deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Novel mechanisms are being explored, such as the transmembrane protein 178, which negatively regulates calcium responses and inflammatory signals in airway epithelial cells. 106 Nevertheless, there are still significant gaps in our knowledge and ability to leverage these pathways for the treatment of asthma and restoration of lung homeostasis. Therefore, further research in this critical aspect of asthma pathogenesis is warranted.…”
Section: Comentioning
confidence: 99%
“…Interestingly, Dr Chiarella's preliminary data show that TMEM178 gene expression in human airway epithelial cells (AECs) decreases with the progression of asthma severity. 9 In addition, he has demonstrated that Tmem178 can regulate ATP-induced intracellular calcium (Ca 21 ) responses in AECs. Finally, in a 4-antigen murine model of asthma, Tmem178 -/mice had higher levels of IL-13, IL-33, and CCL4 mRNA in whole lung than in their wild-type littermates.…”
Section: Sergio E Chiarella MD Winner Of the Aaaai Foundation And Don...mentioning
confidence: 99%